Identification of a pyrovalerone metabolite in the rat by gas chromatography mass spectrometry and determination of pyrovalerone by gas chromatography nitrogen-phosphorus detection - Lho, DS; Lee, J; Kim, S; Park, J; Shin, HS (ELSEVIER SCIENCE BV, 1996)
Pyrovalerone and its hydroxylated metabolite have been identified by gas chromatography-mass spectrometry in rat urine and plasma. A sensitive gas chromatographic method for the quantitative analysis of pyrovalerone in rat urine and plasma is described. The method also permits the quantitative monitoring of the urinary excretion of the drug and its metabolite. Pyrovalerone and its hydroxylated metabolite are detected up to 18 h after a single oral administration to the rat at a dose of 20 mg/kg.